(untitled) (Research, Society and Development, 2022)
Respiratory infections are very prevalent in the pediatric population. The World Health Organization states that respiratory infections are those that occur in the upper and lower respiratory tract, causing infections of nasal, bronchiolar, and pulmonary origin and they are responsible for a high mortality rate in children. The state of Bahia - Brazil is the second state in terms of number of hospitalizations for respiratory diseases in the pediatric population. The clinical picture, for the most part, is nonspecific, making the etiological diagnosis difficult. The conditions usually affect the upper airways, but they can worsen, migrating to the lower airways due to viral infection or co-infection with bacterial agents, mainly by Staphylococcus aureus. Studies to identify the etiological agents are important because they help in asserting the diagnosis, directing the correct use of the drug, favoring the rational use of antibiotics and thus reducing the great problem of bacterial resistance to antimicrobials. This is a cross-sectional, descriptive study by sampling in Juazeiro city, Bahia, through a sample survey of children in the pediatric care services of the municipal network, collecting socio-demographic, epidemiological and event history data, in addition to samples from the nasopharynx. of the patient. From the collection of samples, isolates were screened through microbiological culture. The prevalence of Staphylococcus spp., were isolated. The present study opens a door to new investigations in the reality of the municipality. Other studies can complement and confront the results found.